A Crtitico-Analytical Reading into Natalie Zemon Davis’s Endeavour to Write History through Fiction in The Return of Martin Guerre (1983) - Bendaoud , Fatima Zahra; Bentahar, Soumia (Faculty of Letters and Foreign Languages Department of English, 2023)
The Return of Martin Guerre (1983) by the pioneering American historian Natalie Zemon Davis, has been widely considered as one of the most controversial novels not only because it presents a fictional account of an actual event, but also because it is a novel that is composed by a historian. The latter claims that she invents a new approach to history writing, an approach that blends a historical event with subjective invention. This fact raises the question of how successfully the female author verbalises a possible way of addressing the interplay of the discourses of historicity and fictionality, especially that her being a historian compels her to establish veracity through avoiding any suggestion of subjective intervention. The current dissertation then, seeks to investigate the extent to which Davis, the historian and the novelist, manages to make such interplay possible. In order to achieve this aim, a critio analytical approach is adopted so as to assess whether Davis succeeds at reconciling the supposedly historicity of her book with its constitutive literariness; or, fictionality. This dissertation ultimately concludes that The Return of Martin Guerre does neither embrace the objectivity underlying historical books nor does it meet the appealing quality of fictional narratives